Edukasi Gizi Seimbang dengan Media Video terhadap Pengetahuan dan Sikap Remaja Putri (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2022)
Lack of knowledge and attitudes about balanced nutrition in adolescent girls can cause nutritional problems such as Chronic Energy Deficiency, anemia, obesity, overnutrition. One of the efforts to increase knowledge and attitudes is through nutrition education with video media. Video media is expected to be able to stimulate the senses of hearing and sight during the process of delivering educational materials. The purpose of this study was to determine the effect of balanced nutrition education with videos on the knowledge and attitudes of adolescent girls. The design of this study was quasi-experimental with a one-group pretest-posttest design. The number of samples as many as 24 people who were selected by purposive sampling. The intervention provided education about balanced nutrition with video media. Knowledge and attitude data based on scores obtained through Google Form. Data analysis using Paired T test. The results showed that the average knowledge score increased by 16.04 and the attitude score increased by 4.42. There was a difference in the score of knowledge (p=0.0001) and attitude (p=0.001) before and after the intervention in adolescent girls.